HUMANITARIAN FOUNDATIONS OF THE CONTENT OF EDUCATION AT RIGA CLASSICAL GYMNASIUM IN THE CONTEXT OF THE “EUROPEAN DIMENSION IN EDUCATION” - Aliyev, Roman; Chehlova, Zoja; Chehlov, Mikhail; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the 21st century, humankind has realised that the future of civilization is related to the development of education. A person capable of acquiring knowledge and applying it creatively, as well as being able to participate in the process of creating and using new knowledge, can only be prepared by an effective future-oriented system of education.  Novelty of the research refers to the development of the structure of the content of education in the gymnasium as the relationship between didactics (knowledge and skills) and culture.  Culture is viewed as the interconnection of three cultures: social experience (universal human values), the culture of a student, and the culture of a teacher.  Research problem is the determination of the essence and structure of the content of education in the gymnasium in accordance with the new humanitarian paradigm of education as the relationship between didactics and culture, the basis for the development of student’s personality. The aim of the research is to analyse the humanitarian foundations of the content of education in the gymnasium in the context of the “European dimension in education”. The research method is theoretical analysis. The results of the research are as follows: the humanitarian foundations of the content of education in the gymnasium have been determined; the essence and structure of the content of education have been elaborated. On this basis, an effective system of profile education has been created for the development of student’s personality as a future professional and a European citizen having moral values.  The present study leads to the conclusion that the humanitarian foundations in the content of education correspond to the “European dimension in education”.